Uso de refinamento adaptativo em escultura virtual para criação livre de detalhes em malhas triangulares - Sampaio, Artur Pereira (2011)
Modeling of virtual objects and characters can be tedious and difficult in many situations. A modeling system should be capable of representing any change or feature desired by the user as quickly and transparently as possible, allowing the modeler to focus on the act of creating, as opposed to having to specify the position of each vertex manually. Such a system, if on the one hand offers less control in determining the position of each vertex, being computationally more expensive in some situations, on the other hand greatly simplifies the work of the artist, allowing character modeling to be accessible to any user. This work addressed the problem of traditional sculpting techniques to add details on triangular meshes with adaptive resolution, in regions with low vertex density. The proposed algorithm splits faces and edges in the region of interest of the artist to ensure the existence of a sufficient number of vertices to represent the desired detail, without any additional input requested. The resulting system is capable of bridging the gap between traditional and virtual modeling, improving some of the main methods proposed in the literature regarding the location of the subdivisions. Moreover, it also helps to maintain a good mesh topology and geometric quality, with few vertices of high valence, even if the original mesh is poorly refined, allowing the incorporation of new details.